Synthesis and optical properties of bismuth doped NaTaO3 - Deng, Jiyang (2013)
The main objective of this project is to synthesize Bi doped NaTaO3 and to investigate the structural and optical properties of the synthesized Bi-NaTaO3. [Peer Assessment Review]